The Effectiveness of Valgus Knee Braces and Lateral Wedge Insoles on Gait Parameters in Patients with Medial Knee Osteoarthritis: A Literature Review - Jamehbozorgi, Ali asghar; Rezaei, Mehdi (Journal of Clinical Physiotherapy Research, 2023)
Introduction: Knee osteoarthritis (OA) is a prevalent degenerative joint disease among the elderly. Medial knee OA, characterized by uneven pressure distribution in the knee joint, leads to alterations in gait parameters such as reduced gaite speed, increased knee adduction moment (KAM), and decreased stride length. Valgus knee braces (VKB) and lateral wedge insoles (LWI) are common non-surgical interventions for management of this problem. This literature review aims to compare the effectiveness of VKB and LWI on gait parameters in elders with medial knee OA. Materials and Methods: A literature search was conducted in PubMed, Web of Science, Embase, and Scopus in November 2024. Studies investigating the effects of VKB and LWI on gait parameters such as KAM, walking speed, stride length, and Range of Motion (ROM) were included. Data were synthesized narratively, focusing on the key findings and outcomes of each study. Results: The review included 8 studies with a total of 211 participants. The findings indicated that VKB significantly reduced KAM, whereas the results for LWI were inconsistent. The combination of VKB and LWI resulted in a greater reduction in KAM than either intervention alone. However, neither VKB nor LWI significantly improved walking speed or stride length. Conclusion: VKB are more effective than LWI in reducing KAM, but the combination of both interventions may have synergistic effects. Further studies are needed to explore the long-term effects of these two orthoses on medial knee OA.